Development and characterization of zein edible films incorporated with catechin/β-cyclodextrin inclusion complex nanoparticles. (1st June 2021) - Jiang, Longwei; Jia, Fuguo; Han, Yanlong; Meng, Xiangyi; Xiao, Yawen; Bai, Shigang
Highlights: CINPs were prepard via nanoprecipitation. Zein/CINPs nanocomposite film was prepared and characterized for the first time. The incorporation of CINPs can improve the TS, EBA and WVP of zein film. The nanocomposite film still has strong antioxidant activity after storage. The release behavior of CA from zein film was controlled. Abstract: Zein films incorporated with catechin/β-cyclodextrin inclusion complex nanoparticles (CINPs) were developed, and the structure, physicochemical, antioxidant and release properties of the films were characterized. FT-IR results indicated that intermolecular hydrogen bonds were formed between the CINPs and zein. XRD analysis showed that the addition of CINPs did not change the crystal structure of zein film. SEM images observed that the addition of NPs made zein film surface more smooth and dense. Since the nanoparticles occupy the pores of the film matrix, the swelling degree and water vapor barrier property were improved. CINPs addition significantly increased tensile strength, from 2.28 to 12.49 MPa, and increased elongation at break, from 1.52 % to 4.5 % (p < 0.05). The nanocomposite film still maintains strong antioxidant activity after storage. The release behavior of catechin from zein film was controlled. Therefore, zein composites can be used as a potential antioxidant food packaging film-forming material.